Urinary exosomes derived circRNAs as biomarkers for chronic renal fibrosis. (31st December 2022) - Cao, Yuhan; Shi, Yuanhui; Yang, Yanlang; Wu, Zhangli; Peng, Nana; Xiao, Jie; Dou, Fan; Xu, Jingjing; Pei, Wenjun; Fu, Cong; Chen, Pingsheng; Wang, Yuwei
Abstract: Background: Chronic renal disease (CKD) is a common and irreversible loss of renal function. Renal fibrosis reflected the degree of renal dysfunction. However, the current biomarkers only characterize the renal function instead of indicating the fibrosis degree. The potential diagnostic value of urinary exosomes derived circRNAs for renal fibrosis needs to be further studied. Methods: Urine exosomes from 3 chronic kidney disease (CKD) patients without renal fibrosis and 3 renal fibrotic patients were collected and human circRNAs microarray analysis were performed to detect the circRNAs expression profile. 110 biopsy-proven CKD patients and 54 healthy controls were enrolled and urine exosomes derived RNA was isolated. The expression of hsa_circ_0036649 was measured and the correlation with renal function parameter and pathological indicators was performed. The receiver operating characteristic (ROC) curve for the diagnosis of renal fibrosis was calculated. Results: Human circRNAs microarray showed 365 circRNAs up expressed and 195 circRNAs down expressed in renal fibrotic patients compared to none fibrosis CKD patients. The expression of hsa_circ_0036649 was decreased in renal fibrotic patients according to RT-PCR and correlated with serum creatinine, blood urea nitrogen (BUN), estimated glomerular filtration rate and cystatin c. Further, the expression of hsa_circ_0036649 was correlated with the score of tubulointerstitial fibrosis (TIF) and the score of glomerular sclerosis. The ROC curve showed that hsa_circ_0036649 may predict renal fibrosis at a cut-off value of 0.597 with a sensitivity of 45.5% and specificity of 87.9%. Conclusion: Expression of urinary exosomes derived hsa_circ_0036649 associated with the degree of renal fibrosis. Its potential role as a biomarker in CKD remained to be supported by further follow-up studies. Key Messages: circRNAs profile in urine exosomes in renal fibrosis patients was revealed. The expression of urine exosomes derived hsa_circ_0036649 was correlated to renal function and fibrosis degree. circRNAs derived from urinary exosomes may become a new research direction for biomarkers of renal fibrosis.